(untitled) (Linguist, 2021)
This paper aims to study a central Saussurean concept which is “evolutionary change”. The centrality of the concept of “evolution” stems from its position at an intersection between various Saussurean linguistic concepts appearing either as central heads such as the concept of System, or in dichotomies like synchrony and diachrony, or trichotomies such as langage, speech, and discourse. In fact, the centrality of the concept of linguistic evolution is enough to clarify the depth of Saussure’s conception about the relation between synchrony and diachrony, which is deeply different from the vulgarizing and simplistic approaches, which reduce and shorten the Saussurean project in overtaking the diachrony.